(untitled) (Research, Society and Development, 2021)
Silage is the main forage conservation process, being widely used in periods of low supply of forage in the pasture or in more intensive systems of animal production. Several factors affect the quality of the silage, both at the time of harvest and in the period of storage and opening of the silo, which may cause a reduction in nutritional quality. In this forage conservation, it is essential to control dry matter losses so that the nutrient content does not drastically reduce. There are still other losses in the form of effluents, which are produced by excess humidity; losses in the form of gases resulting from fermentative reactions, producing carbon dioxide which directly interferes with nutritional quality. One of the ways to reduce losses is the use of additives in the silage process, as it will promote an adequate environment for the production of lactic acid and inhibit the growth of deteriorating microorganisms. Thus, it is evident the importance of knowing the losses that are related in the silage process, in order to minimize them and obtain as a result an appropriate silage for use in the animal production system.